Improved In vivo Effect of Chrysin as an Absorption Enhancer Via the Preparation of Ternary Solid Dispersion with Brij®L4 and Aminoclay - Lee, Sang H.; Lee, Yeo-song; Song, Jae Geun; Han, Hyo-Kyung (Current Drug Delivery, 2019)
Background: Chrysin is a strong inhibitor of breast cancer resistance protein (BCRP) but it is practically insoluble in water. Effective solubilization of chrysin is critical for its pharmaceutical application as an absorption enhancer via inhibition of BCRP-mediated drug efflux. Objective: This study aimed to develop an effective oral formulation of chrysin to improve its in vivo effect as an absorption enhancer. Method: Solid dispersions (SDs) of chrysin were prepared with hydrophilic carriers having surface acting properties and a pH modulator. In vitro and in vivo characterizations were performed to select the optimal SDs of chrysin. Results: SDs with Brij®L4 and aminoclay was most effective in increasing the solubility of chrysin by 13-53 fold at varying drug-carrier ratios. Furthermore, SDs significantly improved the dissolution rate and extent of drug release. SDs (chrysin: Brij®L4: aminoclay=1:3:5) achieved approximately 60% and 83% drug release within 1 h and 8 h, respectively, in aqueous medium, while the dissolution of the untreated chrysin was less than 13%. XRD patterns indicated the amorphous state of chrysin in SDs. The SD formulation was effective in improving the bioavailability of topotecan, a BCRP substrate in rats. Following oral administration of topotecan with the SDs of chrysin, the Cmax and AUC of topotecan was enhanced by approximately 2.6- and 2-fold, respectively, while the untreated chrysin had no effect. Conclusion: The SD formulation of chrysin with Brij®L4 and aminoclay appeared to be promising in improving the dissolution of chrysin and enhancing its in vivo effect as an absorption enhancer.
Keywords: Chrysin